PENERAPAN FUNGSI PENGAWASAN DPRD DALAM MEWUJUDKAN PEMERINTAHAN DAERAH YANG BAIK - Taufiq Yuli Purnama; Sigit Sapto Nugroho; Mudji Rahardjo (Universitas Merdeka Madiun, 2023)
Abstract- The purpose of the research is to find out the role of the DPRD's supervisory function in realizing good governance to create a prosperous society as well as the obstacles faced by the DPRD and efforts to strengthen it as a government administration institution on its performance. The type of research used is empirical juridical legal research using primary and secondary data sources, namely through the results of data analysis. By using the data obtained from the survey results, namely interviews and distributing questionnaires. The results of this study indicate that the implementation of the DPRD's supervisory function is carried out by the Commission to review, study and continuously evaluate several aspects that have not gone well. In carrying out its performance towards the Government, of course the DPRD has faced obstacles as well as various efforts to overcome these obstacles. One of the obstacles faced by the DPRD's supervisory function is differences in political interests, inadequate expert staff and laws and regulations that often experience changes. In this case, the efforts made by the supervisory function of the DPRD to overcome the obstacles it faces are by optimizing the role of the DPRD's fittings, the existence of clear and straightforward rules and other things that need to be corrected by the DPRD. As local government partners, the DPRD needs to be sensitive and responsive to the governance management process in the region. With the functions, duties, authorities and rights possessed by the DPRD, it is hoped that it will be able to play its role optimally in controlling the implementation of regional regulations. The goal is to create a regional government that is efficient, clean, authoritative and free from corruption, collusion and nepotism.